Geochemical and mineralogical classification of four new shergottites: NWA 10441, NWA 10818, NWA 11043, and NWA 12335. (27th April 2022) - Orr, Kenneth J.; Forman, Lucy V.; Rankenburg, Kai; Evans, Noreen J.; M Donald, Bradley J.; Godel, Belinda; Benedix, Gretchen K.
Abstract: Martian meteorites are rare; therefore, the discovery of new meteorites has the potential to significantly expand our current understanding of Mars. In this study, we describe four new shergottites, all found within the past 5 yr, in Northwest Africa (NWA): NWA 10441, NWA 10818, NWA 11043, and NWA 12335. To determine the geochemical and mineralogical composition of these new shergottites, a number of traditional and nontraditional analytical techniques were utilized, such as high‐resolution X‐ray computed tomography (for 3‐D modal abundance determination) and electron backscattered diffraction (for identification of shock features). This enabled a comprehensive, nondestructive investigation of the in situ and bulk characteristics of these meteorites. From the results, we confirm the preliminary classifications of NWA 10441 and NWA 12335 as basaltic (diabasic), and NWA 10818 and NWA 11043 as poikilitic, shergottites. Chondrite‐normalized rare earth element (REE) patterns of shergottites distinguish likely source reservoirs in the Martian mantle. NWA 10441 and NWA 12335 have bulk enriched REE patterns. NWA 10818 has an intermediate REE pattern, being slightly depleted in the light REE. Although published data for bulk rock REE in NWA 11043 indicate an enriched pattern, here we show that targeted in situ analyses of unaltered minerals reveal an intermediate REE pattern, suggesting that terrestrial weathering combined with shock processes experienced by these meteorites on ejection may affect the bulk analysis. Extensive fracturing in NWA 11043 likely acted as conduits for terrestrial alteration products. We suggest that in situ spot checking of REE in meteorites will constrain any weathering effect on the REE pattern of the bulk rock.